Polynomial Model Of Transmission And Reflection Of Electromagnetic Waves In Multilayer Thin Films Subjected To An External Transverse Voltage - Elhabbash, Mohammed K. M. (2024)
In designing and controlling the transmission and reflection characteristics of multilayer thin films, mathematical modelling of their electrical and optical response is a vital step to save time, effort and money in the experimental fabrication process. Different approaches exist for modelling the propagation of electromagnetic waves through multilayer thin films. This thesis employs the polynomial approach to model the electromagnetic wave, utilizing dielectric constants, electrical resistivities, and refractive indices of thin film materials to infer the transmission and reflection of electromagnetic wave incidents on the multilayer structure when one or more accumulated-charge regions superimpose between adjacent layers. The model, based on Maxwell's equations was derived for nonmagnetic lossless or lossy materials. Wave Tensor and Wave Tensor-II, home-grown MATLAB codes, were used to simulate the polynomial model for three pairs of materials: pair consists of a non-magnetic lossy material, germanium, and a non-magnetic lossless material, magnesium oxide. Second pair are two non-magnetic lossless materials, magnesium oxide and calcium fluoride. Third pair of materials are two non-magnetic lossless materials: calcium fluoride and silicon dioxide. The dielectric constants, electrical resistivities, and refractive indices of chosen materials were outsourced from trustworthy references.